Hysteroscopic outpatient metroplasty for T-shaped uterus in women with reproductive failure: Results from a large prospective cohort study. (December 2019) - Alonso Pacheco, Luis; Laganà, Antonio Simone; Garzon, Simone; Pérez Garrido, Arantxa; Flores Gornés, Alberto; Ghezzi, Fabio
Abstract: Objective: To evaluate the effectiveness of hysteroscopic outpatient metroplasty in women with T-shaped uterus and primary reproductive failure. Study Design: Prospective cohort study including nulliparous women with primary unexplained infertility, repeated in vitro fertilization (IVF) failure or recurrent spontaneous miscarriage and T-shaped uterus anomaly not diethylstilbestrol-related, diagnosed by 3D ultrasound and diagnostic hysteroscopy. Between January 2015 and December 2017, hysteroscopic metroplasty was performed in outpatient settings with a 5-mm diameter hysteroscope and 5-Fr operative scissors. After 3 months, expectant management was proposed to women with unexplained couple infertility or recurrent spontaneous miscarriages, and IVF treatment was proposed after 6 months without natural conception or immediately to couple with repeated IVF failure. Minimum follow-up was planned for 1 year. Results: A total of 63 women were included, and only 60 tried to conceive after metroplasty. Hysteroscopic procedures were performed without complications. Clinical pregnancy rate after metroplasty was 83.3% (n = 50/60) (p < 0.001), and the live birth rate was 63.3% (n = 38/60) (p < 0.001). Cesarean section rate was 26.3%. No pregnancy complications potentially related to uterine surgery were reported. The abortion rate was 12% (n = 6/50) (p < 0.001). Conclusion: In women with primary reproductive failure and T-shaped uterus, hysteroscopic metroplasty seems to be effective to improve reproductive outcomes.